THE EFFECTIVENESS OF USING GOOGLE CLASSROOM IN IMPROVING STUDENTS’ LISTENING ACHIEVEMENT - Khalisa, Aini Nur; Muliati, A.; G, Hasriani (JTechLP: Journal of Technology in Language Pedagogy, 2024)
The study aimed to evaluate how effectively Google Classroom can improve students' listening skills at SMPN 21 Makassar. A quantitative research method using a pre-experimental design was implemented. The participants were eighth-grade students from SMPN 21 Makassar, with one class chosen from a total of six through cluster random sampling. Specifically, class 8E was selected, which had 20 students. To gather data, listening tests were conducted both before and after the intervention. The collected data were analyzed using a t-test with a significance level set at 0.05. The research revealed a p-value (sig. 2-tailed) of 0.000, which is lower than the significance threshold of 0.05. As a consequence, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Moreover, the effectiveness of Google Classroom, assessed through the N-Gain score, indicated a moderate level of effectiveness. Therefore, the researcher concludes that Google Classroom is relatively effective in enhancing students' listening skills at SMPN 21 Makassar.